Emotions in the Ottoman Empire - Tekgül, Nil. (London)
xi, 169 sayfa
Keywords: “Exploring the political, social and familial ties in early modern Ottoman society, this book is a timely contribution to both the history of emotions and the study of the Ottoman Empire. Spanning compassion in political discourse and shame in judicial courts, to affection in the home, and hate in divorce cases, Emotions in the Ottoman Empire considers the role of emotions in both micro and macro settings. Drawing on Ottoman primary sources such as advice manuals, judicial court records and imperial decrees, this book argues that emotions in early modern Ottoman society were not just linguistic expressions of inner feelings but acted as tools for social and political communication. Using emotions it also reveals the experiences of everyday, ordinary people; why shame was always expressed by men, why gratitude played such an important role in local guilds and why Ottoman women used public baths as emotional refuges. Highlighting a culture that has so far been neglected in the history of emotions, this book looks to globalise the field and think more deeply about Ottoman society in the early modern period.” --